2021
DOI: 10.1111/tmi.13630
|View full text |Cite
|
Sign up to set email alerts
|

Model of care, Noma Children’s Hospital, northwest Nigeria

Abstract: The Nigerian Ministry of Health has been offering care for noma patients for many years at the Noma Children's Hospital (NCH) in Sokoto, northwest Nigeria, and M edecins Sans Fronti eres has supported these initiatives since 2014. The comprehensive model of care consists of four main components: acute care, care for noma sequelae, integrated hospital-based services and communitybased services. The model of care is based on the limited evidence available for prevention and treatment of noma and follows WHO's pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 54 publications
(83 reference statements)
0
9
0
Order By: Relevance
“…If the patient survives the acute illness, they can live into adulthood but often require extensive reconstructive surgery and intensive physiotherapy to improve the resulting structural and functional defects [ 174 ] that often require a number of surgical treatments [ 137 ]. Studies have highlighted the fact that the time between acute illness and surgical care can be decades [ 136 , 141 , 144 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the patient survives the acute illness, they can live into adulthood but often require extensive reconstructive surgery and intensive physiotherapy to improve the resulting structural and functional defects [ 174 ] that often require a number of surgical treatments [ 137 ]. Studies have highlighted the fact that the time between acute illness and surgical care can be decades [ 136 , 141 , 144 ].…”
Section: Resultsmentioning
confidence: 99%
“…Noma often leads to stigmatization and resultant social isolation of the patients and their family members from their communities [ 2 , 14 , 16 , 102 , 156 ]. Several studies have highlighted the importance of including social and psychological support for noma patients and their families [ 136 , 137 , 156 , 169 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite significant progress in scientific methods since these ancient reports, the literature on noma has predominantly been comprised of low level evidence such as case reports [10]. The focus of recent literature on noma (2019-2021) includes noma's distribution and risk factors [17][18][19], treatment [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], knowledge and beliefs about the disease [14,[35][36][37] along with reviews of the literature and viewpoints [38][39][40][41]. Recent literature (2019-2021) has shown that noma cases are being reported from an increasingly diverse set of geographical locations outside of Africa including China [22,28], India [23], Vietnam, [24] and Indonesia [33] (Fig.…”
Section: Neglect Of Noma Researchmentioning
confidence: 99%
“…For many survivors, this stigmatization is the leading reason for seeking care [31,51]. As such, treatment programs should encompass a mental health component [34]. This component should be paired with a concerted effort to sensitize communities by sharing information about noma in an attempt to decrease the stigma survivors' face.…”
Section: Stigma and Discriminationmentioning
confidence: 99%
“…Noma is a ravaging orofacial gangrenous stomatitis which is characterized by acute necrotizing ulcerative lesions (1,2). Noma is prevalent in developing countries where most of the victims are children (3)(4)(5). Epidemiological case study reports have established risk factors for the disease such as poor hygiene and nutritional status, measles and other eruptive fevers and immunocompromising diseases (6,7).…”
Section: Introductionmentioning
confidence: 99%